Bat activity is related to habitat structure and time since prescribed fire in managed pine barrens in New England - Kay, Natalie; Sadlon, Amelia; Bakermans, Marja H. (PeerJ, 2023)
Background Several insectivorous bat species are found in New England, yet research on them is still scarce. Current research shows the ecological importance of bats due to their control of insect populations, but they are endangered by habitat loss and White Nose Syndrome, among other threats. Pine barrens are an uncommon ecosystem found in New England that supports other rare taxa and could be important for these bat species. Methods With hand-held audio recorders, we surveyed for bats in Montague Plains Wildlife Management Area in Massachusetts and Concord Pine Barrens in New Hampshire in June 2022. Our study objectives were to (1) describe the most common bat species and (2) compare bat activity across different habitat types at two managed pine barrens in New England. In particular, we examined bat activity related to habitat type (scrub oak, mature pitch pine, treated pitch pine, hardwood forest), habitat structure (i.e., canopy closure), time since prescribed fire, and path width. We analyzed our data through generalized linear modeling and logistic regression. Results Overall, we were able to measure the presence of five out of the nine total species found in the area, including the endangered Myotis lucifugus (little brown bat). We recorded 293 bat calls, with the majority of calls from big brown bats (71%). We found significant differences (p < 0.05) in bat activity in relation to time since prescribed fire and habitat structure. The index of bat activity was greatest in pitch pine and hardwood forests and lowest in scrub oak and treated pitch pine habitats. With preliminary data, we also found that silver-haired bat presence was influenced by habitat type, with more detections at survey points in hardwood forests. Discussion These findings demonstrate the importance of pine barrens as an ecosystem that supports bats in New England. According to the activity of bats in our study, closed canopy and mature pitch pine habitats may be prioritized in conservation efforts at managed barrens for bat species. Further research is recommended to better understand the relationship between prescribed fires, which are common in managed barrens, and bat activity.
Keywords: Acoustic monitoring; Barrens; Myotis; Pitch pine; Scrub oak; Restoration